Cushing’s disease – cardiovascular and metabolic complications - Marta Izabela Mazur (Pediatria i Medycyna Rodzinna, 2019)
Cushing’s disease is excess cortisol level due to increased adrenocorticotropin secretion from pituitary adenoma. Incidence rate is 2–3 cases per year and the prevalence is 40 per 1 million people. It affects mostly young adults with high prevalence in women (incidence rate is 3–8 fold higher than in men). Cushing’s disease can generate metabolic and cardiovascular complications. Aim: The aim of this paper was to estimate the incidence of cardiometabolic complications, such as hypertension, diabetes, prediabetes, overweight and obesity and their relationships with age, sex and body mass index. Material and methods: A total of 79 presurgical patients with Cushing’s disease were enrolled. All patients were examined and their medical documentation was thoroughly analysed with special regard to demographic data, the underlying disease and concomitant diseases (especially diabetes, prediabetes, hypertension, overweight and obesity). Results: Mean body mass index (BMI) was 31.07 ± 6.97 kg/m2. Obesity (BMI ≥30 kg/m2), overweight (BMI 25–30 kg/m2) and normal body weight were reported in 37 (46.8%), 29 (36.7%) and 13 (16.5%) patients, respectively. Diabetes and prediabetes were diagnosed in 27 (34.2%) and 29 (36.7%) patients, respectively. The remaining 23 (29.1%) patients had normal glucose levels. Hypertension was confirmed in 64 of 79 (81%) patients; 15 (19%) patients had normal blood pressure. Conclusions: Complications like high BMI, impaired glucose metabolism and hypertension were diagnosed in the majority of patients: 66 (83.5%), 56 (70.9%) and 64 (81%), respectively. The risk of these complications increased with age.